Particle swarm optimization: the gradient correction - Borowska, Bożena; Nadolski, Stefan (Wydawnictwo Politechniki Łódzkiej, 2009)
In the following paper, the solution of the optimization problem that relied on the determination of the optimal geometry of two cylindrical coil arrangement evoking magnetic field of specific parameters was presented. The objective of the task was to generate, in a defined active area, the magnetic field of the largest possible gradient and simultaneously keep this gradient relatively constant. The computations were performed using the classical particle swarm optimization as well as the modified method with the correction sensitive to the fitness function gradient introduced to the formula describing the movement of the specific swarm particles. As a result, a considerable enhancement of the optimization process was achieved.